A Rare Case of Early Gastric Mixed NeuroendocrineNon-Neuroendocrine Neoplasm - Yin, Shouxin; Han, Shuai; Ren, Shuangshuang (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Yin S, Han S, Ren S. A rare case of early gastric mixed neuroendocrine-non-neuroendocrine neoplasm. Turk J Gastroenterol. 2025;36(7):474-476.